Analysis of Internal Control in Preventing Accounting Fraud at Al Halim Fastabiqul Khairat Mosque - Rangkuti, Muhammad Idris; Lubis, Haniah; Zuraidah (JAWI : Journal of Ahkam Wa Iqtishad, 2025)
This study analyzes the implementation of internal control in preventing accounting fraud at Masjid Al Halim Fastabiqul Khairat in Pekanbaru. Using a qualitative descriptive approach through field research, the findings reveal that internal control in the mosque includes five main components: control environment, risk assessment, control activities, information and communication, and monitoring. These elements are implemented based on Islamic ethical principles such as amanah (trustworthiness), transparency, justice, and muraqabah (spiritual accountability). Preventive and detective measures are applied to minimize the risk of fraud, including structured approval systems, periodic financial reports, and active community participation. This study concludes that a well-structured internal control system supported by Islamic economic values plays a crucial role in ensuring financial integrity and enhancing public trust in mosque governance. The results provide valuable insight for other religious institutions to strengthen accountability and foster community-based Islamic financial management.